Resposta :
Resposta:
[tex]A = \left( {{1} \: \: \: \: {3} \atop{ - 1} \: \: \: \: {2}} \right) \\ \\ B\left( {{2} \: \: \: \: {4} \atop{ 3} \: \: \: \: {1}} \right) \\ \\A + B = \\ \\ \left( {{1} \: \: \: \: {3} \atop{ - 1} \: \: \: \: {2}} \right) + \left( {{2} \: \: \: \: {4} \atop{ 3} \: \: \: \: {1}} \right) = \\ \\ \left({1 + 2} \: \: \: \: \: \: {3 + 4} \atop{ - 1 + 3} \: \: \: \: \: \: {2 + 1} \right) = \\ \\ \boxed{ \Large \green{A + B = {\left( {{3} \: \: \: \: {7} \atop{2} \: \: \: {3}} \right)}}} \\ \\ \Large\boxed{ \underline{ \blue{ \bf \: Bons \: Estudos!}}}[/tex]